From the hut to civilization: the indians in the colonization process of Roraima in the xx century - Santos, Raimundo Nonato Gomes dos (Textos e Debates, 2016)
This work analyzes the Indian participation in the process of construction of a nonindian place in Roraima, in the twentieth century. We use a diversified material – texts already published and thoughts of Michel de Certeau inasmuch as he defends that reports build places.